Making sense of people and place in linguistic landscapes - Peck, Amiena; Stroud, Christopher; Williams, Quentin (Advances in sociolinguistics., 2019)
"This volume offers comprehensive analyses of how we live continuously in a multiplicity and simultaneity of 'places'. It explores what it means to be in place, the variety of ways in which meanings of place are made and how relationships to others are mediated through the linguistic and material semiotics of place. Drawing on examples of linguistic landscapes (LL) over the world, such as gentrified landscapes in Johannesburg and Brunswick, Mozambican memorializations, volatile train graffiti in Stockholm, Brazilian protest marches, Guadeloupian Creole signs, microscapes of souvenirs in Guinea-Bissau and old landscapes of apartheid in South Africa in contemporary time, this book explores how we are what we are through how we are emplaced. Across these examples, world-leading contributors explore how LLs contribute to the (re)imagining of different selves in the living past (living the past in the present), alternative presents and imagined futures. It focuses particularly on how the LL in all of these mediations is read through emotionality and affect, creating senses of belonging, precarity and hope across a simultaneous multiplicity of worlds. The volume offers a reframing of linguistics landscape research in a geohumanities framework emphasizing negotiations of self in place in LL studies, building upon a rich body of LL research. With over 40 illustrations, it covers various methodological and epistemological issues, such as the need for extended temporal engagement with landscapes, a mobile approach to landscapes and how bodies engage with texts"--